Direct Rehydrogenation of LiBH4 from H-Deficient Li2B12H12−x - Yigang Yan; Hui Wang; Min Zhu; Weitong Cai; Daniel Rentsch; Arndt Remhof (Crystals, 2018)
Li2B12H12 is commonly considered as a boron sink hindering the reversible hydrogen sorption of LiBH4. Recently, in the dehydrogenation process of LiBH4 an amorphous H-deficient Li2B12H12−x phase was observed. In the present study, we investigate the rehydrogenation properties of Li2B12H12−x to form LiBH4. With addition of nanostructured cobalt boride in a 1:1 mass ratio, the rehydrogenation properties of Li2B12H12−x are improved, where LiBH4 forms under milder conditions (e.g., 400 °C, 100 bar H2) with a yield of 68%. The active catalytic species in the reversible sorption reaction is suggested to be nonmetallic CoxB (x = 1) based on 11B MAS NMR experiments and its role has been discussed.